2011
DOI: 10.1111/j.1574-6941.2011.01175.x
|View full text |Cite
|
Sign up to set email alerts
|

Communities of purple sulfur bacteria in a Baltic Sea coastal lagoon analyzed by pufLM gene libraries and the impact of temperature and NaCl concentration in experimental enrichment cultures

Abstract: Shallow coastal waters, where phototrophic purple sulfur bacteria (PSB) regularly form massive blooms, are subjected to massive diurnal and event-driven changes of physicochemical conditions including temperature and salinity. To analyze the ability of PSB to cope with these environmental factors and to compete in complex communities we have studied changes of the environmental community of PSB of a Baltic Sea lagoon under experimental enrichment conditions with controlled variation of temperature and NaCl con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 31 publications
1
28
0
Order By: Relevance
“…In addition to these findings, the pufM gene amplicon analysis has clearly shown that the major phylotypes detected were those assigned to the genera Thiolamprovum and Thiocapsa in the pink mudflat and to Marichromatium and Thiocapsa in the red tide pools. Similar PSB members accompanied by smaller numbers of PNSB and aerobic anoxygenic phototrophic bacteria have been found in massive blooms in a brackish lagoon [8]. To our knowledge, therefore, the formation of red-pink blooms in coastal environments is attributable to massive development of PSB, and the contribution of PNSB as the colorants to the bloom formation is less significant.…”
Section: Discussionsupporting
confidence: 64%
See 3 more Smart Citations
“…In addition to these findings, the pufM gene amplicon analysis has clearly shown that the major phylotypes detected were those assigned to the genera Thiolamprovum and Thiocapsa in the pink mudflat and to Marichromatium and Thiocapsa in the red tide pools. Similar PSB members accompanied by smaller numbers of PNSB and aerobic anoxygenic phototrophic bacteria have been found in massive blooms in a brackish lagoon [8]. To our knowledge, therefore, the formation of red-pink blooms in coastal environments is attributable to massive development of PSB, and the contribution of PNSB as the colorants to the bloom formation is less significant.…”
Section: Discussionsupporting
confidence: 64%
“…The available information on the occurrence of PNSB in colored microbial mats and blooms in the environment has so far been only scattered and fragmentary [8,[19][20][21]. As reported herein, our polyphasic approach to address this issue by culture-independent techniques as well as by conventional cultivation methods has improved information on the distribution of PNSB in colored blooms/mats in terms of quantity and quality.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Although this fraction of the more abundant organisms could be regarded to include the most important players (at least under the conditions and the time of sampling) by no means it represents the potential of a selected sample and habitat under variation of the environmental conditions. In fact, changes of the environmental conditions are expected to provoke significant and complex changes of the community composition with the effect that minor and not detected members of the community become major or even dominant parts of it [ 9 ]. Probably one of the most extreme realizations of this effect is seen in enrichment cultures used by generations of microbiologists to specifically manipulate the natural community.…”
Section: Progress and Limitations Of Sequence Studies Of 16s Rrna mentioning
confidence: 99%